Behavior of Financial Management in Coastal Communities: A Case Study of West-South Aceh Millennials - Damrus; Amsal Irmalis (Pencerah, 2023)
This study aims to analyze the role of attitudes, socialization, experience, and financial literacy in improving financial management behavior in the millennial generation in the south-west coast of Aceh. Lack of knowledge about financial management and lack of awareness of the need to delay consumption (investment) make Indonesian people have financial behaviors that are not ideal. The tendency toward a consumptive lifestyle of the Indonesian people demands a fairly high income. Environmental influences require the community to work as hard as possible in order to meet all needs. This study will use path analysis, which is the development of regression analysis. Based on results and discussion, we can conclude that financial attitude has a strong influence on financial behavior, even though financial literacy is also important. Because it is believed that attitude is more important than knowledge in affecting someone’s behavior in managing money, this research suggests that financial socialization has no impact on financial literacy or behavior. Lastly, when there is a high level of financial literacy, financial experience will have a greater impact on the management funds.